Faktor-Faktor Yang Mempengaruhi Kualitas Pelayanan Publik Di Kantor Desa - Mustamin Mustamin; Siti Atika Rahm; Rahmad Hidayat; Rahma Indriani (Universitas Muhammadiyah Mataram, 2023)
This research was carried out using case studies at the Batuyang Village Office, Pringgabaya District, East Lombok Regency, aiming to determine the factors that can affect the quality of public services. This study attempted to collect primary data using an open direct questionnaire, to 60 respondents, to ask for their assessment regarding 6 factors/variables that affect the quality of public services at the Village Office. The data that was successfully collected, then processed and analyzed with a Likert Scale. The results of the study show that the factors that influence the quality of public services at the Village Office include: the work motivation of the bureaucracy and village apparatus, the ability of village apparatus, social supervision/control, organizational/apparatus behavior, communication and organizational restructuring. According to the respondent's assessment and Likert Scale analysis, the variable that contributes/influences more towards the quality of public services, namely the organizational/apparatus behavior variable is in the Good Category (2.8), then the Good contribution is also followed by the bureaucratic and apparatus work motivation variables as well as the communication variable (2.7), then the variable of the ability of the village apparatus and the variable of social supervision/control (2.6) on the quality of public services, only the organizational restructuring variable whose contribution is not good (2.5). Urgent efforts being made by the Village Government to improve the quality of public services, namely the provision of infrastructure facilities so as to better support public services, such as the availability of online service facilities, creating a Village Information System (SID) and it is time for all villages to have their own websites. Changes in services from a manual system to an online system must be followed by efforts to increase the professionalism of public service officials (village officials) and also need to be revitalized, restructured and deregulated in the field of public services.